Protection or Subordination? Critical Discourse of the Minister of Women Empowerment and Child Protection’s Statement - Dewi Christina Marbun; Dona Putri Metri; Nayla Aulia Lathifah; Nayla Fathiyya Khansa (Universitas Negeri Semarang, 2026)
The statement by the Minister of Women Empowerment and Child Protection (PPPA), Arifah Fauzi, who proposed relocating women-only carriages to the middle of commuter line (KRL) train sets following an accident at Bekasi Timur Station on April 27, 2026, has ignited public controversy. The primary data for this study consists of video recordings of the Minister’s direct statement to journalists in media reports. Arifah constructed her argument by first commending PT KAI’s management, identifying the causes of the accident, and subsequently proposing a gender based solution in response to the incident. This study aims to analyze the gender ideology produced through the statement while reinterpreting the Minister’s subsequent apology regarding the resulting controversy. Utilizing Fairclough’s model of Critical Discourse Analysis (CDA), which encompasses three dimensions text, discursive practice, and social practice this study analyzes two primary data units: the Minister’s oral statement to journalists on April 28, 2026, and the official apology statement issued via the Ministry of PPPA’s Instagram channel on April 29, 2026. The results indicate that the initial statement reproduced a patriarchal ideology that positions women as objects of state structural protection rather than as subjects entitled to safety. Furthermore, the analysis of the apology reveals that it did not deconstruct this patriarchal ideology but served merely as a strategy for institutional crisis management. This study contributes to the understanding of how gender ideology functions within the discourse of public officials in Indonesia, while simultaneously demonstrating the application of audiovisual analysis within critical discourse studies.